2008
DOI: 10.1002/cncr.23722
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with pegylated interferon–α‐2a and dacarbazine in patients with advanced metastatic melanoma

Abstract: BACKGROUND.Dacarbazine (DTIC) and pegylated interferon (IFN)–α‐2a have both demonstrated some efficacy as single agents in metastatic melanoma. To the authors' knowledge, the current study is the first to test a combination of these 2 agents in a phase 2 trial.METHODS.Twenty–eight patients with stage IV melanoma without brain metastases were treated with DTIC (at a dose of 850 mg/m2 every 3 weeks) combined with weekly pegylated IFN–α‐2a at a dose of 180 μg. The study was initiated to evaluate the efficacy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…In particular, it has been reported that the melanoma cell density in metastases and angiogenesis was significant reduced after a treatment with IFN-α [131] . melanoma without brain metastases have revealed that a combination of dacarbazine plus pegylated IFN-α2a was well tolerated and associated with a response rate of 24% in 25 patients evaluable for response, including 2 long-lasting complete responses [132] . Interestingly, the results of a phase II trial with an oncolytic herpes simplex virus type 1 encoding granulocyte macrophage-colony stimulating factor (GM-CSF), designated as Oncovex (GM-CSF), have also indicated a 28% objective response rate occurred in patients with melanomas which was accompanied by a tumor regression of both injected and non-injected lesions [126,127] .…”
Section: Immunotherapy-based Strategiesmentioning
confidence: 99%
“…In particular, it has been reported that the melanoma cell density in metastases and angiogenesis was significant reduced after a treatment with IFN-α [131] . melanoma without brain metastases have revealed that a combination of dacarbazine plus pegylated IFN-α2a was well tolerated and associated with a response rate of 24% in 25 patients evaluable for response, including 2 long-lasting complete responses [132] . Interestingly, the results of a phase II trial with an oncolytic herpes simplex virus type 1 encoding granulocyte macrophage-colony stimulating factor (GM-CSF), designated as Oncovex (GM-CSF), have also indicated a 28% objective response rate occurred in patients with melanomas which was accompanied by a tumor regression of both injected and non-injected lesions [126,127] .…”
Section: Immunotherapy-based Strategiesmentioning
confidence: 99%
“…Many studies have used PEG IFN- α , a form of IFN- α that has been modified to have a longer half-life and thus have a greater opportunity to reduce angiogeneses [209]. A phase I trial completed tested the effect of subcutaneous injections of PEG IFN- α and recombinant IL-2 in patients with metastatic RCC [210].…”
Section: Normal Blood Vessel Formationmentioning
confidence: 99%
“…A phase II trial then investigated the use of Dacarbazine (DTIC) alongside PEG IFN- α for the treatment of metastatic melanomas. Of the 25 patients who completed the study, 8% had complete remission from the treatment, while another 16% had partial responses [209]. Stable disease was found in 4% of patients while 72% had their disease progress.…”
Section: Normal Blood Vessel Formationmentioning
confidence: 99%
“…117 Patients were treated with 850 mg/m 2 DTIC every 3 weeks combined with 180 μg PegIFNα-2α weekly. Only 50% of the patients participating in the study had received previous adjuvant therapy with IFN-α.…”
Section: Pegifn In Combination With Chemotherapymentioning
confidence: 99%
“…Median progression-free survival was 56 days, median duration of response was 236 days and OS time was 403 days. 117 Of interest is the fact that 6 out of 7 patients who showed CR or PR or developed SD had not received IFN adjuvant treatment in the past or progressed to stage IV melanoma during IFN treatment.…”
Section: Pegifn In Combination With Chemotherapymentioning
confidence: 99%